Continuous professional development for librarians - Yeap , Ai-Ling (Persatuan Pustakawan Malaysia, 2009)
In order to keep up with developments within the profession, librarians need to continuosly upgrade their knowledge and skills. This can be done through various methods. This article discusses the need and importance of continuous professional development for librarians.